NEW WOOD FOAM-HEAT INSULATING MATERIAL OBTAINED THROUGH OAK WOOD-DELIGNIFICATION PROCESS (Nonconventional Technologies Review, 2023)
A technique for manufacturing wood heat-insulating material for construction (known as wood delignification) without seriously affecting the cellulosic structure was inspired by the practices of the pulp and paper industry and adapted to the mentioned purpose. Among the numerous known methods of chemical treatment of wood for removing the lignin in the paper industry, the use of the suspension generated by mixing of NaOH, Ca(OH)2, and distilled water at 260 ℃ in an electric oven was adopted. For the first time, oak wood (recycled in the form of sawdust) was chosen as the basic raw material in the wood delignification process due to its large availability in Romania's climatic conditions. Using 58 % oak wood, 23.3 % NaOH, 16.7 % Ca(OH)2, and water addition, the best product had very low values of density (0,024 g·cm-3) and heat conductivity (0.031          W·m-1·K-1) as well as an acceptable value of compression resistance (0.9 MPa) for construction applications.
Keywords: wood delignification; heat-insulating; oak wood; chemical treatment; density; heat conductivity